2018
DOI: 10.3389/fphys.2018.00270
|View full text |Cite
|
Sign up to set email alerts
|

The Hyperglycemic Effect of Melatonin in the Chinese Mitten Crab, Eriocheir sinensis

Abstract: Melatonin has been identified in a variety of invertebrate species, but its function is not as well understood as in crustaceans. The effects of melatonin on hemolymph glucose levels and tissue carbohydrate metabolism in the Chinese mitten crab, Eriocheir sinensis, were fully investigated in this study. Moreover, whether the eyestalk (an important endocrine center in invertebrate species) involves in this process or not, also were clarified. Analysis revealed that eyestalk ablation, especially bilateral, cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 52 publications
(64 reference statements)
1
8
0
Order By: Relevance
“…The 10 –6 , 10 –8 , and 10 –10 mol/crab 5-HT injection groups were named as 10 –6 , 10 –8 , and 10 –10 mol 5-HT, respectively. The 10 –6 , 10 –8 , and 10 –10 mol/crab DA injection groups were named as 10 –6 , 10 –8 , and 10 –10 mol DA, respectively. , Each crab was injected in the third pereiopod with 20 μL of crustacean saline, which contained the drugs . According to reports, injected 5-HT is rapidly distributed throughout the hemolymph, and most (75%) is cleared from the hemolymph via tissue uptake and/or binding within 5 min after injection in crayfish .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 10 –6 , 10 –8 , and 10 –10 mol/crab 5-HT injection groups were named as 10 –6 , 10 –8 , and 10 –10 mol 5-HT, respectively. The 10 –6 , 10 –8 , and 10 –10 mol/crab DA injection groups were named as 10 –6 , 10 –8 , and 10 –10 mol DA, respectively. , Each crab was injected in the third pereiopod with 20 μL of crustacean saline, which contained the drugs . According to reports, injected 5-HT is rapidly distributed throughout the hemolymph, and most (75%) is cleared from the hemolymph via tissue uptake and/or binding within 5 min after injection in crayfish .…”
Section: Methodsmentioning
confidence: 99%
“…39,53 Each crab was injected in the third pereiopod with 20 μL of crustacean saline, which contained the drugs. 54 According to reports, injected 5-HT is rapidly distributed throughout the hemolymph, and most (75%) is cleared from the hemolymph via tissue uptake and/or binding within 5 min after injection in crayfish. 11 Based that study, after drug injection, the crabs were placed in water for 10 min, and crabs that were injected with the same dose of a drug were used to observe agonistic behavior according to the description in the section "Pairing".…”
Section: Methodsmentioning
confidence: 99%
“…Melatonin can affect the physiological functions of the hepatopancreas in crustaceans. For instance, melatonin affects blood glucose in crustaceans (Yang et al, 2018); the secretion of melatonin can also promote digestive enzyme function (Cong et al, 2018) and immunity (Balzer et al, 2012). Based on these correlations, we suggest that the circadian rhythms of hepatopancreas metabolites and their physiological functions in E .…”
Section: Discussionmentioning
confidence: 99%
“…As to melatonin actions in crustaceans, it has already been demonstrated that the indoleamine plays a role in limb regeneration ( Tilden et al, 1997 ), ecdysteroid production ( Sainath S. B. and Reddy P. S., 2010 ; Girish et al, 2015 ), antioxidant defense ( Maciel et al, 2010 ; Geihs et al, 2016 ; She et al, 2019 ), color change ( Nery et al, 1999 ), locomotor activity ( Geihs et al, 2010 ), and hyperglycemia ( Sainath SB. and Reddy PS., 2010 ; Maciel et al, 2014 ; Yang et al, 2018 ), among others. Many melatonin functions in crustaceans are related to the molt cycle, as shown by the increased levels of ecdysteroids in melatonin-treated Y-organ cells ( Girish et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%